Unlocking Students’ Experience on Listening Practice in English for Nursing Context - Audi Yundayani (International Journal of Practical and Pedagogical Issues in English Education)
Listening skills are an essential aspect of English for nursing purposes, and they involve the capacity to understand spoken language. It allows nurses, as healthcare providers, to communicate with English-speaking patients to understand their condition better and provide higher-quality treatment. Nevertheless, most nursing students require assistance with English listening practice even though their English proficiency appears satisfactory. Furthermore, additional research is required to investigate the application of listening in nursing. The following article highlights the nursing students' experiences with listening practice in English for nursing courses. The respondents of this investigation are forty-one nursing students from a public Polytechnic of Health in Jakarta. The data was collected through a survey and a semi-structured interview, and the qualitative analysis was conducted afterward. The research identified students' perspectives regarding English listening practices for nursing purposes, including their strategies for overcoming English listening challenges and the listening media they employ in their listening strategies within the nursing context, including the use any digital-based applications installed on Android devices. The student's learning engagement is enhanced, which motivates them when their learning preferences align with the listening activities. Moreover, English teachers can use these research findings to create an English listening course for nursing students.